Jilbab, Cadar, dan Tubuh: Pertarungan Makna dalam Ruang Publik melalui Perspektif Konstruktivisme Sosial - Nazila Ramadana; Rica Amelia Putri; Surawan Surawan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The hijab and niqab in Indonesia often spark debates that go beyond clothing choices, touching on identity, religious authority, and social structures that shape public perceptions. This study examines how the meanings of the hijab, niqab, and women’s bodies are constructed, contested, and negotiated in public spaces from a social constructivist perspective. Using a qualitative method with critical discourse analysis, data were gathered through literature review, online media analysis, and limited interviews with students and community members holding diverse views. This approach helps uncover hidden meanings embedded in texts, symbols, and social practices. Findings reveal that the hijab and niqab do not hold uniform meanings. Some communities regard them as expressions of piety and religious identity, while others perceive them as symbols of restriction. These contested meanings intensify in public arenas such as social media, where religious, cultural, and political narratives intersect. The study highlights the fluid, context-dependent nature of these symbols and their role in shaping religious and gender identities in Indonesia.